Microsoft Visual Basic 2010 developer's handbook - Löffelmann, Klaus (O'Reilly Media, 2011)
"This book is a reference on language concepts and features, as well as scenario-based guidance for putting Visual Basic to work. For use whether you're creating new applications with Visual Basic 2010 or upgrading projects built with an earlier version of the language"--Page 4 of cover.